If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + -1w = 3 Combine like terms: 2w + -1w = 1w 1w = 3 Solving 1w = 3 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Divide each side by '1'. w = 3 Simplifying w = 3
| 8x^3-18x= | | x^3+11x^2+10x= | | 3x^2-15x+18= | | 3a-4=9 | | 2y^2-8y+2=0 | | 0=x^4-36x^2 | | 4m^2-18m+14= | | 15m^3+24m^2+9m= | | w+3=5 | | -(5y+1)-(-4y-7)=2 | | 2w=5 | | 102-6x=21x+15 | | 15m^2-10m-25= | | 5x+5=-150-10x | | y=ty | | 12=-3s | | 50m^3-2m= | | 2w-w=4 | | 3m^2-10m+8= | | 10n^2-3n-1= | | x^2-18x=72 | | 2w-w=5 | | 1-9n^4= | | s+34=14 | | 2w+1-w=5 | | 2n^2+11n+15= | | 2n^2+11a+15= | | 2.13x=10 | | 5n^2+9n-2= | | n^2+4n-21= | | n^2+4a-21= | | 4+(x+0)= |